The Potency of Moringa Leaf Extract (Moringa oleifera L.) In a Facial Treatment Mist Formulation Over Acne and Bacteria - Indriastuti, Marlina; Listyani, Tia; Wahlanto, Panji; Setiawan, Doni; Harun, Nurhidayati; Kurniasih, Nia; Riski, Radhia (LPPM STIKes Muhammadiyah Ciamis, 2025)
Background: It is often known that moringa leaves (Moringa oleifera L.) are a natural substance with many advantages, especially for their antibacterial qualities that prevent the growth of bacteria. Objectives: The main objective of this study was to evaluate the efficacy of particular face mist preparation made from Moringa leaf extract in inhibiting the growth of Propionibacterium acnes, the bacteria that causes facial acne. Methods: A facial mist containing moringa extract was created, and its antibacterial qualities were assessed using the Kirby-Bauer technique in conjuction with the agar duffision method. Results: The face mist preparation effectively satiated the homogeneity, pH, viscosity, and spray pattern physical assesment criteria in the organoleptic test. Conclusions: Strong anti-acne and antibacterial properties were present in the face mist preparation made from moringa leaf extract, especially at a concentration of 45% that sucesfully stopped the growth of all test.